Excellent performance in hydrogenation of esters over Cu/ZrO2 catalyst prepared by bio-derived salicylic acid. Issue 19 (26th July 2016) - Ding, Jian; Liu, Yanting; Zhang, Juan; Liu, Kefeng; Xiao, Haicheng; Kong, Fanhua; Sun, Yanping; Chen, Jiangang
Abstract : A variety of bio-derived organic carboxylic acids are used to prepare Cu/ZrO2 . In particular, salicylic acid provides superb control over the distribution of small Cu particles on t-ZrO2, which affords enhanced catalytic activity. Abstract : Herein, Cu/ZrO2 catalysts have been prepared using bio-derived organic carboxylic acids (ORCOOH) as complex agents. The one using salicylic acid (SA) as a complex agent exhibits both small CuO particles and abundant crystalline ZrO2, regardless of being calcined at 550 or 750 °C. As a result, the catalyst calcined at 550 °C shows excellent selectivities towards ethanol of 93.1% and 98.9% in the hydrogenation of dimethyl oxalate (DMO) and ethyl acetate under higher weight liquid hourly space velocity, respectively. Besides, a selectivity towards ethylene glycol of 97.9%, which corresponds to 100% conversion of DMO, is achieved over the catalyst calcined at 750 °C. In this case, a high turnover frequency of 64.5 h −1 is maintained over more than 120 h on stream. In brief, the aromatic ring skeleton with a large conjugated π-system in SA influenced the structures and properties of the obtained complexes. After thermal treatment, the interaction between Cu and crystalline ZrO2 further supports retention of higher metal dispersion to improve the catalytic activity.